A comparative study on the enzymatic biodegradability of covalently functionalized double- and multi-walled carbon nanotubes. (April 2016) - Modugno, Gloria; Ksar, Fayçal; Battigelli, Alessia; Russier, Julie; Lonchambon, Pierre; Eleto da Silva, Edelma; Ménard-Moyon, Cécilia; Soula, Brigitte; Galibert, Anne-Marie; Pinault, Mathieu; Flahaut, Emmanuel; Mayne-L'Hermite, Martine; et al.
Abstract: The assessment of the biodegradability potential of carbon nanotubes (CNTs) is a fundamental point towards their applications in materials science and biomedicine. Due to the continuous concerns about the fate of such type of nanomaterials, it is very important to understand if they can undergo degradation under certain conditions and if the morphology and structure of the nanotubes play a role in this process. For this purpose we have decided to undertake a comparative study on the enzymatic degradation of CNTs with concentric multilayers. Double-walled (DW) and multi-walled (MW) CNTs of various lengths, degrees of oxidation and functionalizations using different methods were treated with horseradish peroxidase (HRP). While all tested DWCNTs resulted resistant to the biodegradation, some of the MWCNTs were partially degraded by the enzyme. We have found that short oxidized multi-walled CNTs functionalized by amidation were reduced in length and presented a high amount of defects at the end of the period of treatment with HRP. This comparative study holds its importance in the understanding of the structural changes of different types of nanotubes towards the catalytic enzymatic degradation and will help to design safer CNTs for future applications.